Cognitive function in long-term lymphoma survivors: relationship between subjective reports and objective assessments and with quality of life. Issue 8 (14th September 2021) - Muzzatti, Barbara; Cattaruzza, Nicoletta; Piccinin, Marika; Flaiban, Cristiana; Agostinelli, Giulia; Berretta, Massimiliano; Annunziata, Maria Antonietta
ABSTRACT: Cognitive functioning plays a fundamental role in people's life and quality of life (QoL), and anti-cancer chemotherapy may provoke long-lasting cognitive problems. This study investigated the subjective perception of cognitive functioning in long-term lynfoma survivors and its associations with objectively assessed cognitive functioning and QoL. 198 long-term lynfoma survivors were administered the Cognitive Functioning Self-Assessment Scale (CFSS), the Esame Neuropsicologico Breve 2 (ENB2) and the Short Form 36 Health Survey Questionnaire (SF-36). Subjectively reported cognitive functioning was worse than the norm for the general population ( p <0.001). Difficulty in recalling recent information (22%), using of periphrases or generic terms (16.7%) and tip-of-the-tongue phenomena (14.7%) were the cognitive difficulties most frequently reported. CFSS overall score correlated positively with the number of impaired performances ( p <0.001) and borderline performances ( p =0.014) on the ENB2. Both subjectively and objectively assessed cognitive measures correlated negatively with most assessed QoL domains, indicating that QoL is worse when cognitive functioning is poor. Subjective concerns about one's own cognitive functioning are a reality for long-term lynphoma survivors, who experience these worries more than the general population does. Since improving QoL is a priority in oncology, this study supports the use of interventions to improve cognitive functioning in cancer survivors.